Sociodemographic and medical influences on neurobehavioral patterns in preterm infants: A multi-center study. (March 2020) - McGowan, Elisabeth C.; Hofheimer, Julie A.; O'Shea, T. Michael; Carter, Brian S.; Helderman, Jennifer; Neal, Charles R.; Pastyrnak, Steve; Smith, Lynne M.; Soliman, Antoine; Dansereau, Lynne M.; Della Grotta, Sheri A.; Lester, Barry M.
Abstract: Background: Among preterm infants, neurodevelopmental outcomes are influenced by both medical and sociodemographic factors. Less is known about the impact on these factors on neonatal neurobehavioral patterns. Objective: To determine associations between demographic, psychosocial and medical risk factors and neonatal neurobehavior. Methods: Multi-center observational study of infants born <30 weeks enrolled in the Neonatal Neurobehavior and Outcomes in Very Preterm Infants (NOVI) Study between April 2014–May 2016. Maternal medical, demographic, and psychological variables and infant medical variables were prospectively collected. Demographic, substance, psychological and medical risk indices were developed. Neurobehavioral assessment was performed using the NICU Network Neurobehavioral Scale (NNNS) at NICU discharge. Results: 709 infants were enrolled in the NOVI study, and for 679 infants with neurobehavioral assessments, 6 NNNS behavioral profiles were calculated using latent profile analysis. Profile 6 infants ( n = 47/679, 7%) were atypical, having poor attention, self-regulation and movement quality, hypertonia and increased stress signs. After adjustment for site, profile 6 infants had significantly smaller head circumferences at birth (β −0.87; −1.59, −0.14), and higher rates of late sepsis (OR 3.38; CI 1.66, 6.92) compared to Profiles 1–5 infants. There were no significant differences in other neonatal morbidities between the two groups. Profile 6 infants had a higher prenatal demographic risk score (1.46 vs 1.07;β 0.34; CI 0.06, 0.61) compared to Profiles 1–5 infants. Conclusion: NNNS behavioral profiles identify an atypical behavioral pattern that is associated with early influences of demographic and medical variables. Such behavioral patterns may be seen as early as NICU discharge. Highlights: Neurobehavioral assessment can capture signs of atypical behavior in preterm infants. Sepsis and small head circumference are associated with atypical neurobehavior. Increased sociodemographic risk may also alter infant neurobehavior. Prior to hospital discharge such neurobehavioral changes may be identified. Recognition of atypical neurobehavioral patterns offers insight brain developmental.